Adversarial process: urgent problems of modern Russian criminal proceedings - Vyacheslav V. Koryakovtsev; Xenia V. Pitulko (Правоприменение, 2019)
The subject of the article is realization of adversarial process principle in Russian criminal proceedings.The purpose of the article is to disclose the list of systemic flaws in modern criminal justice. The hypothesis of the study is the thesis that the ongoing transformation of the criminal procedure did not lead to its transformation on the basis of the principle of the adversarial process.The authors use formal‐legal and comparative‐legal methods as well as legal interpretation of the text of Russian Criminal Procedure Code and Russian Constitutional Court’s decisions.The main results and scope of their application. The problem field of the research is the analysis of the latest changes in the Criminal Procedure Code of the Russian Federation and their influence on the qualitative modernization of the domestic justice. For optimal understanding of the problem field, the authors used a set of general scientific and private‐scientific methods. The article provides a brief overview of the legal positions of the Constitutional Court of the Russian Federation and judicial acts reflecting the views of the law enforcers on the motivation of the sentence. In the introduction, the authors justify the relevance of the study, also discusses possible criteria for the fairness of a judicial decision in criminal justice. The second section analyzes the main trends in overcoming the accusatory bias in criminal proceedings and determines the relationship between constitutional legal and criminal procedural parameters of justice and the validity of judicial decisions. The third section examines the main shortcomings of the elements of judicial control in pre‐trial criminal proceedings and assesses the prospects for the establishment of an investigative judge. In the fourth section, the authors explore the specifics of the legalization of operative information as evidence in a criminal case, taking into account the legal positions of the Constitutional Court. The fifth section is devoted to the analysis of the latest changes in the criminal procedure law regarding the order of consideration of cases in the appellate and cassation instances. In the sixth section, the dynamics of doctrinal views on the systemic flaws of the Russian criminal process are examined.The main proposals for the improvement of the Russian criminal procedure legislation are formulated in the conclusion. It is concluded that the principle of the adversarial process is not taken into consideration completely during the transformation of the criminal procedure in Russia.